Sosialisasi Sistem Keamanan Perimeter Bandara di Indonesia - Endang Sugih Arti; Sri Rahayu Surtiningtyas; R.B. Budi Kartika W; Nunuk Praptiningsih; Dini Wagini (Politeknik Penerbangan Indonesia Curug, 2023)
Aims to provide solutions to the problems that exist in the Budiarto Airport Operator Unit (UPBU) and several other airports in Indonesia which are still facing the same condition, there are wild animals which disturbed traffic on the runway, and its necessary to disseminate information to the surrounding community. Budiarto Airport and others airports in Indonesia in order to Minister of Transportation Regulation Number PM 33 of 2015 concerning Access Control to Limited Security Areas at Airports, and amendments to Permenhub No. 167 of 2015, PM 51 of 2020 concerning National Aviation Security, PM 51 of 2020 concerning the National Aviation Security, With the number of participants, approximately 80 people the Budiarto Airport Operator Unit (UPBU) who attended from the four closest villages, (Serdang Wetan, Serdang Kulon, Palasari, Kemuning), as well as the Tangerang Transportation Agency, Pondok Cabe Airport, Babo Airport in Papua,Aceh Malikus Saleh Airport, Mopah Merauke Papua International Airport, Rendani Manokwari Airport and Ngloram Cepu Airport via Zoom Meeting so that people around the airport could help maintain flight security and safety in the area of aircraft movement.